2009
DOI: 10.1007/s11219-008-9066-3
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the utility of web development methods

Abstract: Although many web development methods exist, they are rarely used by practitioners. The work reported here, seeks to explain why this might be so, and suggests that, for many, the perceived benefits may be outweighed by the difficulty or effort required to learn the method. In attempting to gauge the utility of methods the authors undertook a 2-year study of 23 small web development projects, attempting to use a range of published (academic) methods. Of the 23 projects we found only one case where the develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(200 reference statements)
0
3
0
Order By: Relevance
“…As previously reported, web development methods are difficult to use for novice developers [4] however, a number of the students identified with two elements of WSDM [23] that the students believed could be used to good effect in any method. The framework is shown at Figure1.…”
Section: The Creation Of a Requirements Frameworkmentioning
confidence: 73%
See 1 more Smart Citation
“…As previously reported, web development methods are difficult to use for novice developers [4] however, a number of the students identified with two elements of WSDM [23] that the students believed could be used to good effect in any method. The framework is shown at Figure1.…”
Section: The Creation Of a Requirements Frameworkmentioning
confidence: 73%
“…We have previously divided these differences into three areas [4]: the user domain, the developer and development team domain and finally, the environment. The user domain is of particular interest to the requirements engineer because the web at the interface is of primary importance to the user and is an area where there are a number of differences.…”
Section: Introductionmentioning
confidence: 99%
“…He and his team conducted a case study. They concluded that the introduction and need of Fagan inspection technique have a lot of importance as well as benefits [7]. After that a researcher Ferreira focused that software inspection finds and removes only those defects that are close to the injection point.…”
Section: Literature Reviewmentioning
confidence: 99%